70 years of Sergey Apollonovich Nikitov - Butov, Oleg Vladislavovich; Dmitriev, Aleksandr Sergeevich (Известия высших учебных заведений: Прикладная нелинейная динамика)
On April 23, 2025, Sergey Apollonovich Nikitov, an outstanding scientist in the field of solid-state electronics, academician of the Russian Academy of Sciences, celebrated his 70th birthday.